Poétique du cratylisme et identité culturelle dans Monnè, outrages et défis d’Ahmadou Kourouma - Jean Marius Ehui; Kassoume Touré (Multilinguales)
The present study aims to analyze the anthroponymic and toponymic practice of Ahmadou Kourouma, particularly in his novelistic story Monnè, outrages et défis. The objective of such an analysis, which will be carried out in the light of poetics, is to show that the proper names, of people or places, participate in constructing the meaning of the text from a referential discourse. In general, the onomastic approach in a literary text highlights its anthropological and social dimension. The work of Ahmadou Kourouma is a perfect illustration of this. In this, anthroponymic and toponymic uses not only participate in cultural and identity marking strategies but they also underlie the literariness of the text.